PENGARUH DISIPLIN BELAJAR DAN LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS X IPS - Aprilla, Dhea; Achmadi, Achmadi; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The purpose of this study is to determine the effect of the learning environment and learning discipline on the economics learning outcomes for class X IPS students at SMA Islam Bawari Pontianak. A quantitative methodology approach was used in this investigation. As the sample, 50 students were involved. In this study, the data were analyzed using multiple linear regression analysis, and they were also collected using questionnaires and a simple random sample technique. (1) The significance value of 0.0440.05 and the regression coefficient value of 0.313, which was positive, along with the Tcount Ttable being 2.069 2.011, indicated that learning discipline had a significant impact on the learning outcomes. (2) The regression coefficient value of 0.317, the significance value of 0.042, and the Tcount Ttable of 2.095 2.011 all indicate that the learning environment has a substantial impact on the learning outcomes. (3) With an F value of 10.922 and a significance level of 0.000, there is a simultaneous substantial relationship between the learning environment and the learning discipline on the learning outcomes of economic subjects in class X IPS SMA Islam Bawari Pontianak. The learning environment and learning discipline's overall effect on class X students at IPS SMA Islam Bawari Pontianak's economics classes is 31.7%.